Dynamics of Brazil Current dipoles: barotropic instabilities and flow-western boundary interactions - Miranda, Juliana Albertoni de (2013)
This dissertation examines the nature of jet-boundary interactions and the role of barotropic instabilities in the Brazil Current system while still attached to the western boundary. The motivation was due to the frequent observation of bipolar features associated to the Brazil Current flow south of Cape Frio (RJ) and off Santos Bight (22º-28ºS). Such observations were mainly obtained from sea surface temperature images, and also from few \"in situ\" hydrographic and direct velocity measurements data. Therefore, our main focus is on the formation of bipolar features associated with the flow, and the main hypothesis is that barotropic instability is responsible for the generation of such dipoles along the western boundary current jet, while it has to deal with topographic variations along its path poleward. We address the system dynamics from a semi-theoretical perspective, and also through the application of numerical modeling on a process study approach. So it includes semi-theoretical studies of jet-lateral boundary interactions in idealized configurations relevant to the Brazil Current system off Cape Frio, considering the quasi-geostrophic theory as an appropriate approximation of the system we want to investigate. Additionally, numerical modeling is used through the construction of idealized scenarios where we simplify the physics in order to isolate the dynamical process of interest. All the dynamical analyzes were initialized from synoptic hydrographic data set which comprised the Brazil Current system off Cape Frio region. We validated the quasi-geostrophic theory we assumed and obtained the kinematics characteristics of the jet. In the dynamical analyses, we started the investigation from the simplest framework applied here, where we evaluate a piecewise constant potential vorticity field in a quasi-geostrophic contour dynamics model. It dealt with a meridionally-oriented jet flowing southward along a straight western boundary. Next, in a second model, we added more complexity in the system, idealizing western boundary coastline scenarios considering a quasi-continuous potential vorticity field in a quasi-geostrophic numerical model. Finally, in a third model, we constructed a more complex scenario for the Brazil Current jet that incorporated real topography and stratification of the water column in a primitive equation numerical model. Among our main finds, we verified that purely barotropic instability is able to generate vortex dipoles. Moreover, variations in the western boundary can indeed trigger perturbations in the jet and dipoles form. Therefore, sites with abrupt change in bathymetry and coastline orientation are preferred to the formation of the BC vortical dipoles. Vortex streets and instability trains can also develop downstream of such locations as consequence of perturbing a potentially batropically unstable jet. Hence, the horizontal shear is key to the generation of vortex dipoles. A weak shear does not allow these features to form, instead, frontal eddies are possibly generated, with the predominance of anticyclones. Although the three different model strategies applied here differ in dynamical configurations and approximations, they still kept nearly the same regime for the Brazil Current vortex-dipole formation. Topographic variations such as those associated with the change of coastline orientation near Cape Frio (23ºS) account for those vortex dipoles and streets be dominantly observed within the Santos Bight.